2013
DOI: 10.3233/jad-131409
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development of Dementia in a Unique Six-Year Cohort Study. I. An Exploratory, Pilot Study of Involvement of the E4 Allele of Apolipoprotein E, Mutations of the Hemochromatosis-HFE Gene, Type 2 Diabetes, and Stroke

Abstract: Risk factors for dementia development are not well-defined. We evaluated several factors alone and in combination in a unique cohort of Caucasian volunteers over an approximately 6-year observation window using a nested case/control design. Factors included: apolipoprotein E (ApoE) gene variants (the E4 allele is the strongest confirmed genetic predisposing factor for Alzheimer's disease), the hemochromatosis-HFE gene mutations (H63D and C282Y), diabetes, and stroke. At study entry, subjects were ≥65 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 90 publications
3
14
2
Order By: Relevance
“…We did not replicate the previous finding of an effect of HFE SNPs on risk of AD and an epistatic interaction for risk with APOE ε4 genotype, but we cannot yet rule out an association of HFE SNPs with AD age of onset or phenotypic interactions [25,27,28].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not replicate the previous finding of an effect of HFE SNPs on risk of AD and an epistatic interaction for risk with APOE ε4 genotype, but we cannot yet rule out an association of HFE SNPs with AD age of onset or phenotypic interactions [25,27,28].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies previously reported an increased frequency of the HFE H63D (rs1799945) mutation in AD patients [25], but these findings have not been replicated in the largest AD GWAS meta-analysis [26]. There is evidence of interaction effects, which would not be apparent in GWAS meta-analyses, involving H63D and APOE ε4 alleles where the combination appears to affect age of onset and, to a lesser extent, risk [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Whether this increased risk is augmented by ApoE ε4 carrier status for general dementia or only restricted to risk of AD is unresolved [4,8]. Several studies investigating the interaction between ApoE and lifestyle risk factors regarding dementia risk have been hampered by a low statistical power by including too few subjects with later dementia; typically, the studies have 30-130 cases [4,9,10,11,12,13,14]. For example, the Finnish CAIDE study investigated ApoE ε4 and lifestyle-related factors, such as physical activity [12], alcohol use [13] and fat intake [14], and risk of dementia, but with 50-120 cases included.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alzheimer's disease has more than 200 genes that might be involved in its pathogenesis (Cacabelos, 2008). In general, only apolipoprotein E4 gene is consistent between studies as the strongest genetic risk factor linked tomost common dementia subtype in various populations (Harold et al, 2009;Percy et al, 2014;Alzheimer's Association, 2017).…”
Section: Introductionmentioning
confidence: 92%